2020
DOI: 10.1177/0264619620941885
|View full text |Cite
|
Sign up to set email alerts
|

Social support for students with visual impairments in educational institutions: An integrative literature review

Abstract: Students with visual impairments often experience emotional problems and encounter difficulties in forming and maintaining social relationships. Research indicates that the social support provided to these students by staff members and their peers in educational institutions may have a positive impact on their academic learning and socioemotional development. The purpose of this integrative literature review was to synthesise the results from 17 academic articles published during 1998 and 2018, which examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…In their final conclusions, the authors stressed the need for future studies focusing on promising interventions where the efficacy is not yet clear, such as mobility and social skills. A second literature review (Manitsa & Doikou, 2020) concentrated on the types of social support delivered individually to students with visual impairments and no additional disability in educational institutions. Out of the 17 studies considered, the authors reported positive effects for 8 studies using educational interventions to improve diverse social inclusion domains for these students.…”
mentioning
confidence: 99%
“…In their final conclusions, the authors stressed the need for future studies focusing on promising interventions where the efficacy is not yet clear, such as mobility and social skills. A second literature review (Manitsa & Doikou, 2020) concentrated on the types of social support delivered individually to students with visual impairments and no additional disability in educational institutions. Out of the 17 studies considered, the authors reported positive effects for 8 studies using educational interventions to improve diverse social inclusion domains for these students.…”
mentioning
confidence: 99%
“…Perceived social support refers to the subjective perceptions and beliefs about the social support received by individuals (Lakey and Scoboria, 2005). Based on their integrative literature review, Manitsa and Doikou (2022) summarized the major themes in existing research on social support for students with visual impairment including their experiences of social support in schools and universities and the impact of these social support on their academic learning and socioemotional development.…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented in the literature that social support contributed to socioemotional development of students with visual impairment (see Manitsa and Doikou, 2022 for a detailed review). However, existing studies are mainly cross-sectional, and research on the unique influence of various sources of social support is insufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research to date on individuals with visual impairment generally focuses on children (Ball et al, 2022; Manista & Doikou, 2022; Philip et al, 2022) or older adults with visual impairment (Liu & Chang, 2020; Nastasi, 2020; Smallfield & Kadenberg, 2020). Little research addresses the lives of middle-aged persons with visual impairment (Caputo et al, 2022; Lund & Cmar, 2019) as services typically are provided upon onset of visual impairment at birth or as an older adult with age-related vision loss.…”
Section: Introductionmentioning
confidence: 99%